PRICES, MARKETS, CORPORATIZATION: GAME-THEORETIC MODELING OF STRATEGIES FOR CORPORATIZED STATE-OWNED ENTERPRISES IN UKRAINE’S TRANSPORT SECTOR - Dunayev, Igor (Social Economics, 2025)
The article focuses on the topical issue of corporatization of state-owned enterprises in Ukraine’s transport sector, particularly Ukrainian Railways (UZ) and the Ukrainian Sea Ports Authority (USPA), in the context of their adaptation to new global challenges and post-war economic recovery. Based on an analysis of contemporary scientific literature, the study substantiates the feasibility of applying game theory tools to model strategic interactions among key stakeholders (government, enterprise management, regulators, investors, and consumers) in the corporatization process. The research aims to assess the potential consequences of completing the corporatization of UZ and USPA for corporate pricing policies, market efficiency, and public welfare using game-theoretic modeling and comparative analysis. The research methodology combines methods of descriptive statistics, systematic literature review, case studies, game-theoretic modeling, and scenario analysis. The developed game-theoretic model allows formalizing strategic interactions among players, evaluating the impact of various corporatization scenarios on key performance indicators, and formulating recommendations for optimizing UZ and USPA’s pricing strategies to balance commercial and public interests. The study argues that transitioning to «infrastructure holding company» models for railways and «landlord port» models for seaports is the optimal format for corporatizing UZ and USPA, enabling the attraction of private investments, enhancing efficiency and service quality while maintaining the state’s strategic control over infrastructure. The necessity of synchronizing corporatization with reforming the regulatory system, tariff policy, and fostering competition in transport services markets is emphasized. The research findings have practical value for developing state policies on leveraging the results of transport infrastructure corporatization and ensuring the sustainable development of Ukraine’s railway and port industries in the post-war period.